Colitis-Associated Cancer - Kusunoki, Masato (Springer Japan : Imprint: Springer, 2016)
As the number of patients with colitis-associated cancer (CAC) is on the increase, the purpose of this book is to review the latest topics concerning management of the disease. In recent years, the diagnostic power of endoscopy and molecular pathology has also grown tremendously, as a result of which they now have a far greater influence on the treatment of CAC. At the moment, appropriate monitoring programs for ulcerative colitis and Crohn's disease remain uncertain. At the same time, the latest findings on DNA methylation and microRNAs hold the promise of making revolutionary changes in these areas. Moreover, recent drug advances in the treatment of inflammatory bowel diseases have changed surgical indications. On the other hand, the indication of mucosectomy on colorectal cancer in ulcerative colitis and prophylactic abdominoperineal resection for Crohn's disease remain controversial. This book provides the latest information on the remaining issues of CAC from the point of view of expert surgeons.